2013
DOI: 10.2106/jbjs.l.00137
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Recombinant Human Bone Morphogenetic Protein-2 in Single-Level Posterior Lumbar Interbody Arthrodesis

Abstract: This trial showed no clinical difference when rhBMP-2 was used in posterior lumbar interbody arthrodesis compared with autologous bone. On computed tomography scans, fusion was equally achieved, but trabecular bone formation occurred at a slower rate and interbody bone density was lower within the first year after surgery when rhBMP-2 was used. End-plate resorption, osteolysis, and ectopic bone formation were frequently noted in the rhBMP-2 group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 1 publication
1
30
0
Order By: Relevance
“…From the potentially relevant 78 publications, 59 were omitted according to the inclusion criteria. Finally, 19 trials [14][32] were included in the meta-analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the potentially relevant 78 publications, 59 were omitted according to the inclusion criteria. Finally, 19 trials [14][32] were included in the meta-analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 12 of the 19 trials met the criteria for a low RoB [14][18], [23], [27][32]. 6 studies have adequate methods of randomization [14], [19], [23], [28], [29], [31], and only two studies use both an adequate sequence generation and allocation procedure [29], [31].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 33 studies (seven level I [109][110][111][112][113][114][115] , eight level II [116][117][118][119][120][121][122][123] , eight level III [124][125][126][127][128][129][130][131] , nine level IV [132][133][134][135][136][137][138][139][140] , one unclassified 141 ) were identified pertaining to rhBMP-2 use in the lumbar spine alone. The sheer volume of literature on rhBMP-2 reflects its acceptance and popularity as a widely used fusion enhancer, as well as the controversial nature of this compound associated with specific complication profiles.…”
Section: Recombinant Bone Morphogenic Protein-2 (Rhbmp-2) In Lumbar Smentioning
confidence: 99%
“…After a level I randomized controlled study, Michielsen et al 109 reported results in 40 patients treated with an instrumented single-level posterior lumbar interbody arthrodesis. Interbody arthrodesis was performed using polyether-ether-ketone (PEEK) cages which were filled with 8 mg of rhBMP-2 in the study group and 2.5 mL of autologous bone in the control group.…”
Section: Recombinant Bone Morphogenic Protein-2 (Rhbmp-2) In Lumbar Smentioning
confidence: 99%
“…Evidence of increased cancer incidence is inconclusive" [59]. More recently, Adams et al [60] and Michielsen et al [61] in PLIF using rhBMP-2 versus local bone autograft found an equivalent effect with an increased risk of complication.…”
Section: Graftmentioning
confidence: 99%